Fifty Years of Family Planning in the Democratic Republic of the Congo : The Dogged Pursuit of Progress. - Bertrand, Jane T. (Routledge Studies on Gender and Sexuality in Africa Series, 2024)
This book chronicles 50 years of struggle to introduce family planning into the Democratic Republic of the Congo. Interweaving details of major political, social, and economic events into the history of family planning in DRC, the book will interest development and public health researchers and practitioners, as well as DRC historians.